PENERJEMAHAN KOMIK MAHASISWA : TINJAUAN ASPEK GENETIK, OBJEKTIF DAN AFEKTIF - Oktavia Dwi Astuti, Dies; Agustiningrum, Tri Eko; Kholid; M.A.R, Saidatina (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study is to describe the genetic aspects, objective aspects and affective aspects of French Language Education study programme students, Universitas Negeri Semarang in translating comics and their readability level. The theory used to analyse the data in this study is the theory of genetic aspects, objective aspects, affective aspects from M.R. Nababan. The results showed that, first, genetic aspects, objective aspects and affective aspects are interrelated and must be mastered by students. Genetic aspect refers to the ability of students as translators to make decisions in translation. This decision-making includes the selection of words, terms, sentence construction, addition or omission of expressions and others. The objective aspect refers to the students' translated works, namely the translated comics. The comic as the result of student translation shows its readability level. The affective aspect refers to the reader's response to the translation (comics). Second, based on genetic aspects, objective aspects, and affective aspects, the level of readability of student-translated comics is dominated by the level of readability that is at the easy level. then followed by the level of readability of difficult, very difficult, and very easy.